Pengaruh Beban Kerja dan Pengembangan Karir terhadap Kepuasan Kerja Karyawan PT. X Surabaya - Valencia Renita Agrippina; Sulastri Irbayuni (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of workload and career development on employee job satisfaction at PT X Surabaya. The research method used was a quantitative survey approach. The sample size was 87 respondents, determined using a saturated sampling technique. Data collection was conducted through a Likert-scale questionnaire, while data analysis used Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of the SmartPLS application through outer and inner model testing. The results showed that workload had a negative and significant effect on employee job satisfaction, with a path coefficient of -0.075 and a p-value of 0.031 (<0.05). Career development had a positive and significant effect on employee job satisfaction, with a path coefficient of 0.798 and a p-value of 0.000 (<0.05). The R-Square value of 0.616 indicates that workload and career development can explain 61.6% of the variation in employee job satisfaction, while the remaining 38.4% is influenced by other factors outside the study. The conclusion of this study indicates that proportional workload management and the implementation of a fair, transparent, and sustainable career development system play a significant role in increasing employee job satisfaction, with career development being the variable with a more dominant influence than workload.   Keywords: Workload, Job Satisfaction, Employees, Career Development